"Low-pressure vs. Standard-pressure pneumoperitoneum in laparoscopic cholecystectomy: A systematic review and meta-analysis". - Sahu, Swaroop Sanat; Kumar, Hitesh; Raj, Kisslay; Singh, Nalini; Toppo, Ashush; Anand, Rakesh; Kachhap, Dr. Deepak Kumar (Student’s Journal of Health Research Africa, 2025)
Background: Laparoscopic cholecystectomy is the preferred treatment for symptomatic gallstones. Standard pneumoperitoneum pressure (12–15 mmHg) ensures adequate visualization but may increase postoperative pain and cardiopulmonary stress. Low-pressure pneumoperitoneum (LPP; 7–10 mmHg) has been proposed to reduce these complications, though its safety and efficacy remain debated. Aim: To compare low- and standard-pressure pneumoperitoneum regarding postoperative pain, recovery, complications, and operative time in laparoscopic cholecystectomy. Methods: Databases including PubMed, Scopus, Cochrane Library, Web of Science, and Google Scholar were searched through July 2025 for randomized controlled trials comparing LPP with standard pressure. Two reviewers independently extracted data. A random-effects model was applied, with heterogeneity assessed using the I² statistic. Publication bias was evaluated by Egger’s test and funnel plots. Results: Fifteen RCTs involving 2,304 patients were included. LPP significantly reduced postoperative pain at 6 hours (MD = –1.24; 95% CI = –1.76 to –0.71; I² = 44%) and 24 hours (MD = –0.98; 95% CI = –1.46 to –0.50; I² = 68%). Conversion rates (OR = 1.03; 95% CI = 0.67–1.58; I² = 0%) and operative times (MD = +2.1 min; 95% CI = –0.9 to +5.1; I² = 28%) were comparable. Hospital stay was slightly shorter with LPP (MD = –0.4 days; 95% CI = –0.7 to –0.1; I² = 59%). Minor publication bias was detected for 24-hour pain (p = 0.04). Conclusion: Low-pressure pneumoperitoneum is a safe and effective alternative to the standard technique, offering reduced postoperative pain and faster recovery without increased surgical risk. Recommendations: Further multicenter RCTs should explore long-term outcomes, cost-effectiveness, and patient satisfaction to support routine clinical use.